PERAN DAN FAKTOR PERKEMBANGAN PERPUSTAKAAN ISLAM DALAM PERADABAN ISLAM PADA MASA KLASIK - Dwi Arsita Mursalim; Andi Abdul Hamzah; Darussalam Syamsuddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to understand the role and factors in the development of Islamic libraries in Islamic civilization during the classical period, a time when science experienced significant growth. The method applied in this article is descriptive and qualitative, and is based on a literature review, namely the analysis of theories related to issues or problems raised regarding the role and factors in the development of Islamic libraries in Islamic civilization during the classical period. The results of this study indicate that libraries in the classical Islamic civilization played a crucial role in intellectual development, not only as a place to store books, but also as an arena for discussion, collaboration, and innovation among intellectuals from diverse backgrounds. In the journey from the classical to the digital era (OPAC), lessons from the classical Islamic era encourage us to revive libraries as a force for change in the modern era, with a similar spirit of engagement and innovation to face today's challenges.